Translation of al-Quran into Malay Language in the Malay World - Hussin, Mohamad; Kamal, Muhammad Hakim (Universitas Ahmad Dahlan, 2021)
The spread of Islam in the Malay Archipelago (henceforth Nusantara) contributed to the activity of al -Quran translation in Malay civilisation. The society started to learn about Islam and the syariah that encouraged them to be close to al-Quran and translate it into the local language. Al-Quran was translated into Malay language in many ways. This study is a study of text aimed at identifying the translated works of al-Quran in Malay language beginning from the 17th century to the 20th century and to investigate its design and chronology. This qualitative study takes a descriptive approach and inculcates the historical method involving heuristics, critique of sources, interpretation and historiography in data collection and data analysis. The research findings show that 21 al-Quran translations into Malay language have been produced since the 17th century in Nusantara. Most of the al-Quran translated works were approached by interpretive translation rather than literal translation. The design of al-Quran translation into Malay language had developed in line with the times, beginning with classical Malay language using the jawi (Arabic) script, until the modern Malay language using romanised script. The concise translation style was seen to dominate the layout of al-Quran translations into Malay language. The al-Quran translation activity was not without controversy, until it led to several works being banned from publication. The rapid translation activity shows the enthusiastic efforts by society in Nusantara in transferring religious knowledge into guidance for daily life.